Pattern of clinical manifestation and antibiotics sensitivity of Burkholderia Cepacia sepsis in Neonatal Intensive Care Unit of tertiary care centre of North India - Bansal, Sharad; Sharma, Rambabu; Jangir, Narendra (International Journal of Contemporary Pediatrics, 2019)
Background: Neonatal sepsis is a major cause of morbidity and mortality worldwide. Now a days, neonatal sepsis due to Burkholderia cepacia is on rise. This study was conducted to delineate clinical presentation and antibiotic sensitivity pattern from blood culture proven Burkholderia sepsis. Methods: In this retrospective analytical study, thirty-six neonates admitted to Neonatal Intensive Care Unit of a tertiary care hospital with blood culture proven Burkholderia sepsis were included. Clinical manifestation, laboratory findings and antibiotic sensitivity patterns of blood culture proven Burkholderia sepsis were analyzed. Results: : All neonates were inborn and were admitted within 24 hours of birth. Difficulty in breathing was most common presenting symptom and seizure was second in number. There was no association with mode of delivery. Male to female ratio is 1.4:1. Progressive thrombocytopenia was the most consistent feature and in 6 patients also associated with anaemia. Average hospital stay was increased and more in preterm neonates. In this setup piperacillin + tazobactem was found to be most sensitive against Burkholderia cepacia and cotrimoxazole was 2nd in sensitivity. Conclusions: Proper and timely identification of Non Fermentative Gram Negative Bacilli (NFGNB) other than Pseudomonas can help confine morbidity due to such infections. High degree of suspicion helps in early recognition. Efficient housekeeping is necessary to prevent nosocomial infections due to these pathogens.